Process Simulation of Wet Flue Gas Desulfurization - Li, Changhong; Zhang, Baiqiang; Li, Junhui; Hu, Yanhao (Journal of Chemical Engineering Research Updates, 2024)
During combustion in power plants, sulfur in coal forms SO2, a key air pollutant causing acid rain. Denitrification of SO2 in exhaust gases is crucial, and simulation is a practical research approach. This article applies Aspen Plus software to simulate and optimize the limestone-gypsum wet flue gas desulfurization process. The results show that the established model can effectively reduce SO2 content, achieving a desulfurization rate of 95.9%, which verifies the feasibility of the process flow. Through sensitivity analysis and orthogonal experiments, it is found that the inlet temperature of flue gas, calcium-sulfur ratio, and water content in limestone slurry are the key factors affecting the desulfurization efficiency. The optimal operating parameter combination is an inlet temperature of flue gas of 80°C, a calcium-sulfur ratio of 1.03, and water content in limestone slurry of 35 kmol/hr, with the calcium-sulfur ratio having the most significant impact on desulfurization efficiency. The study indicates that the combination of this software and the process has good application prospects.